Agreement Between the Iron Path App and a Linear Position Transducer for Measuring Average Concentric Velocity and Range of Motion of Barbell Exercises. (February 2021) - Kasovic, Jovana; Martin, Benjamin; Carzoli, Joseph P.; Zourdos, Michael C.; Fahs, Christopher A.
Abstract : Abstract: Kasovic, J, Martin, B, Carzoli, JP, Zourdos, MC, and Fahs, CA. Agreement between the Iron Path app and a linear position transducer for measuring average concentric velocity and range of motion of barbell exercises. J Strength Cond Res 35(2S): S95–S101, 2021—The purpose of this study was to compare average concentric velocity (ACV) and range of motion (ROM) values measured by the Iron Path (IP) app to the previously validated Open Barbell System (OBS) linear position transducer during the front and back squat and conventional and sumo deadlift. Twenty-seven men and women (21 ± 3 years old; 76.7 ± 14.5 kg; 1.72 ± 0.09 m) with squat and deadlift training experience completed a modified one repetition maximum protocol on 4 separate occasions in a randomized order. The IP app and OBS device recorded ACV and ROM during each protocol. The level of statistical significant was set at p ⩽ 0.05. Bland–Altman plots showed fairly large limits of agreement for both ACV and ROM. Furthermore, 95% confidence intervals for the intraclass correlation coefficients indicated the agreement in ACV between the devices for each of the 4 lifts to range from 0.648–0.876 to 0.849–0.930 and for agreement in ROM between devices to range from −0.053–0.480 to 0.545–0.770. Compared with the OBS, the IP app recorded significantly ( p < 0.05) lower ACV values for the front squat and back squat and greater ROM values for the sumo deadlift. We suggest the IP app should not be used in place of a validated linear position transducer for measuring ACV or ROM for barbell lifts.